Numerical Study Of Turbulent Natural Convection In An Enclosure With Localized Heating From Left Side - Ali L. Ekaid (Engineering and Technology Journal, 2009)
In this work, a numerical study is performed to predict the solution of buoyancy turbulent flow and heat transfer inside a square cavity with localized heating from the left side wall. Full Navier Stockes and energy equations were solved using Finite volume method with a non-uniform staggered grid. The studied Rayleigh numbers wereranged between 1E108 to 1E1012 and Pr=0.72. For the purpose of the analysis, the heated dimensionless length L/H is varied from 0.2 to 0.8. The k-ε model with standard wall function is used to treat the turbulence in the flow. The obtained results show that the strength of the induced recirculating velocity is increased with the increase of Ra. Also the results displaced that the average Nu is increased with the increase of Ra. However the average Nu number is decreased with increasing of dimensionless heated length